Understanding the Social Worker Experience with Organizational Changes in HSOs During the COVID-19 Pandemic - Reyes, José L.; Cederbaum, Julie A.; de Saxe Zerden, Lisa; Zelnick, Jennifer R.; Ross, Abigail M. (Administration in social work, 2025)
Drawing on Lewin's three-stage change theory (i.e. unfreezing, changing, and refreezing), this study explored social workers' experience with organizational changes in human service organizations during the first wave of the COVID-19 pandemic. A qualitative content analysis was conducted using secondary data from a cross-sectional survey (June-August 2020). Responses for 2447 participants (78.5%) who answered the open-ended question, "How have services, functions or operations changed in response to COVID-19?" were thematically coded. Four overarching themes were identified and discussed: (1) changes to organization capacity; (2) technology/infrastructure and workers arrangements; (3) workplace safety; and (4) impact on clients and workers.